Absurdity, Twitter Comedy, and Humor Bots - Sundén, Jenny; Paasonen, Susanna (Oxford University Press, 2025)
This chapter explores the world of Twitter bots (on the verge of Elon Musk’s rebranding and decision to charge for the platform’s API) from a particular angle: that of absurd humor. It builds on and advances discussions of absurd humor in general—and feminist and queer humor and absurdity in particular—by studying Twitter bots as part of a landscape where absurd humor is generated in algorithmic assemblages of human imagination and nonhuman repetition and randomness. It explores a strategic selection of humorous Twitter bot accounts, combined with background interviews with two of their creators, operating with slightly different logics: Gender of the day (@genderoftheday), which generated imaginative, poetic, and charmingly nonsensical takes on what the gender of the day could be when capaciously envisioned; a bookish kind of humor generated by Victorian queerbot (@queerstreet), which scoured digitized nineteenth-century novels for the terms “gay” and “queer”; and the eerie flora and fauna coined by the fabulously surrealist poetry bot British Gardens (@GardensBritish). The absurd represents the opposite of reason, rationality, and meaning, as its etymological Latin root, absurdus (“out of tune, uncouth, inappropriate, ridiculous”), suggests. Following this semantic route, absurd humor is out of harmony with reason and notions of decency. The chapter focuses on what happens to such incongruity when it involves not only people but algorithms, and what may be learned about the pleasures of repetition, randomness, and surprise and the minor mundane affective lifts this affords by studying the bots’ output.
The Oxford Handbook of Screen Comedy